Coping with floods : the experience of rural women in Bangladesh : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University - Begum, Mahbuba; Begum, Mahbuba (Massey University, 1995)
This study focuses on how rural women in Bangladesh, who live in the poorest sector of one of the poorest countries in the world, cope with floods. It seeks to explain the principal factors structuring their responses. It addresses several related questions: how do women perceive and experience floods? What problems do they face and how do they respond to them? Arc they merely the passive victims of floods or do they play an active role in protecting their households? Do all women use the same coping strategies? Are the major parameters of rural society changed as a consequence of the way in which women cope with floods? In responding to these questions a sociological perspective is adopted but not to the exclusion of other approaches. However, it is the social and sociological aspects of the phenomena being explored which are of most concern to the author. The occurrence of floods in Bangladesh is as old as its history but over the last 40 years (1954-1995) the problem has become greatly aggravated and is now one of the main concerns of most rural households, life in which is precarious even in non-flood conditions. These problems affect women more severely than men because of the wider range of responsibilities that they have for their households and the fact that those responsibilities keep them tied to their households more strictly and more effectively than those of male members. Those responsibilities include food processing and cooking, cleaning, collecting water and fuel, bearing and rearing children, looking after livestock and income generation, all of which become much more difficult to perform under flood conditions. Despite this heavy burden, which women bear in extremely difficult circumstances, they demonstrate considerable fortitude and ingenuity in their attempts to maintain the livelihoods of their households. Explanation of these phenomena is sought in the economic, cultural and political structure of the country. Factors stressed in this study are the male-dominated structures of a predominantly conservative and Muslim society; the dominance of parda in the sub-culture of women and the position of women within the socio-economic context of their households.
Keywords: Bangladeshi women; Flooding; Environmental effects; Rural women; Rural poor